ARUS BALIK: GERAKAN FUNDAMENTALIS DALAM ISLAM - Mathias Daven (Jurnal Ledalero, 2014)
There is a strong link between religious fundamentalist movements and the globalization (economic) project. In the context of Western civilization, fundamentalist movements are closely linked to the “critical discussion” on the antinomy of modernity. These movements reached a new phase in the second half of the 20 century, namely a “confrontation” between Western civilization and the East (Islam). On the one hand, the Western civilization model of the globalization project grows due to a certain form of fundamentalism within itself, namely an economic fundamentalism. On the other hand fundamentalist movements within Islam which turn religion into ideology, put forward a programme for the “universalisation” of Islam as the basis of a world order. The world order which is presently dominated by the Western civilization model, characterized by the capitalistic and the secular, has to end and be replaced by a world order based on Islamic law. This movement works on a principle of compulsion. The “rivalry” between the two has no connection at all with a “clash of civilizations” but rather with the fact that globalization in its present form is only possible for a rich elite minority. A middle way must be worked out, not the globalization of the economic or political system, nor the globalization of a particular ideology, whether secular or religious, but rather the globalization of Aufklärung (enlightenment) and of solidarity. Kata-kata kunci: Globalisasi, modernitas, gerakan fundamentalis, islamisme, ideologi, Aufklärung, “imperialisme budaya”, sekularisasi.